Non-fused Phospholes as Fluorescent Probes for Imaging of Lipid Droplets in Living Cells - Öberg, Elisabet; Appelqvist, Hanna; Nilsson, K. Peter R. (Frontiers in Chemistry, 2017)
Molecular tools for fluorescent imaging of specific compartments in cells are essential for understanding the function and activity of cells. Here, we report the synthesis of a series of pyridyl- and thienyl-substituted phospholes and the evaluation of these dyes for fluorescent imaging of cells. The thienyl-substituted phospholes proved to be successful for staining of cultured normal and malignant cells due to their fluorescent properties and low toxicity. Co-staining experiments demonstrated that these probes target lipid droplets, which are, lipid-storage organelles found in the cytosol of nearly all cell types. Our findings confirm that thienyl-substituted phospholes can be utilized as fluorescent tools for vital staining of cells, and we foresee that these fluorescent dyes might be used in studies to unravel the roles that lipid droplets play in cellular physiology and their role in diseases.